Working memory training in pediatric brain tumor survivors after recent diagnosis: Challenges and initial effects. Issue 3 (3rd July 2022) - Siciliano, Rachel E.; Thigpen, Jennifer C.; Desjardins, Leandra; Cook, Jessica L.; Steele, Ellen H.; Gruhn, Meredith A.; Ichinose, Megan; Park, Sohee; Esbenshade, Adam J.; Pastakia, Devang; Wellons, John C.; Compas, Bruce E.
Abstract: Research shows promise for cognitive interventions for children diagnosed with brain tumors. Interventions have been delivered approximately 5 years postdiagnosis on average, yet recent evidence shows cognitive deficits may appear near diagnosis. The present study assessed the feasibility and initial effects of working memory training in children with brain tumors delivered soon after diagnosis and followed 2 years postdiagnosis. Children completed baseline assessments 10 months postdiagnosis and were randomized to complete adaptive or nonadaptive (i.e., control) Cogmed Working Memory Training. Children were administered the WISC-IV Working Memory Index (WMI) and NIH Toolbox Cognitive Battery (NTCB), and parents completed attentional and executive function measures at four time points. On average, participants completed half of prescribed Cogmed sessions. Retention for the three follow-up assessments proved difficult. For both Cogmed groups, WMI and NTCB scores significantly improved immediately postintervention compared to baseline scores. Significant differences were not maintained at the remaining follow-ups. There was preliminary evidence for improved executive function at the final follow-up on parent-reported measures. Working memory training closer to diagnosis proved difficult, though results suggest evidence of cognitive improvement. Future studies should continue to examine potentially efficacious interventions for children with brain tumors and optimal delivery windows to maximize impact.